Therapists’ problematic experiences when working with obsessive-compulsive disorder: a qualitative investigation of schema modes, mode cycles, and strategies to return to healthy adult mode - Semeniuc, Suzana; Sterie, Maria Cristina; Soponaru, Camelia; Butnaru, Simona; Gavrilovici, Ovidiu (Frontiers in Psychiatry, 2023)
Obsessive-compulsive disorder (OCD) is one of the most challenging pathologies for therapists, being chronic and often characterized by frequent relapses. The therapeutic relationship plays a critical role in the outcome of therapy. The dynamic interaction between therapist and client schema modes determine the quality of the relationship.The objective of the present qualitative research is to investigate and conceptualize the triggers for therapists when working with OCD clients, the therapists' schema modes that are activated and the strategies they use to get back into the Healthy Adult.Method: Using the in-depth interview technique we interviewed 15 psychotherapists of various therapeutic orientations. After several demographic items, the therapists answered some introductory questions about their general perceptions of working with this pathology. They were then guided to go through a specific therapeutic situation in imagery that they identified as particularly difficult to manage in the therapeutic relationship. For data analysis, we used Interpretative phenomenological analysis (IPA) method and thematic analysis.Results: For therapists working with clients with OCD, two main categories of triggers have been identified: Perceived resistance to change and Superiority. Two other categories, Immobilized by conflict and Abusive, emerged from our analysis. Therapists' reactions to triggers were synthesized into mode processes that (1) not acted on and (2) were displayed in relation with the client. For mode processes that therapists did not explicitly act on, there was triggering of the Vulnerable Child in relationship with a Demanding Parent, followed by various coping modes, depending on the category of trigger, in the displayed mode most therapists operated in the Healthy Adult mode. With respect to This is a provisional file, not the final typeset article the process, strategies used by therapists to return to Healthy Adult mode that stood out were: focusing on the process, self-acceptance, self-compassion, as well as somatic grounding strategies and focusing on the client's resources.